Self-intercalated metallic transition metal dichalcogenide for high current density water splitting - Long, Yan (Nanyang Technological University, 2023)
Hydrogen has been considered one of the most versatile and environment-friendly energy sources, making it a rising star as an alternative to conventional nonrenewable energy resources, i.e., fossil fuels. One of the main advantages of hydrogen fuel is that it produces only water vapor as a byproduct, making it a zero-carbon emission fuel with promising reduction of emissions for greenhouse gas and air pollutants. Green hydrogen can be produced through water-splitting driven by electricity converted from other types of clean energy, such as solar and wind. Hydrogen evolution reaction (HER) as the half-reaction occurring at the cathodic electrode in water electrolysis processes, it yields H₂ gas as the main product [1]. However, there are also challenges associated with hydrogen production efficiency via HER, which require ongoing research and development efforts further to advance its viability as a mainstream energy source. In particular, the conventional catalysts based on noble metal (e.g., Pt) for HER significantly limit the worldwide deployment of green hydrogen as they are expensive and not readily available [4]. Therefore, there is an urgent need to develop earth-abundant, sustainable, cost-effective, and highly efficient alternative electrocatalysts in order to scale up the industrial yielding of H2.